2011
DOI: 10.4103/0974-1216.114078
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between laparoscopically assisted vaginal hysterectomy and vaginal hysterectomy: Experience in a tertiary diabetes care hospital in Bangladesh

Abstract: Objective:The study was undertaken to compare the efficiency and outcome of Laparoscopic Assisted Vaginal Hysterectomy (LAVH) and Vaginal Hysterectomy (VH) in terms of operative time, cost, estimated blood loss, hospital stay, quantity of analgesia use, intra- and postoperative complication rates and patients recovery.Materials and Methods:A total of 500 diabetic patients were prospectively collected in the study period from January 2005 through January 2009. The performance of LAVH was compared with that of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Nevertheless this bearing on cost could be overcome by early return to work after LAVH. 10 Main drawbacks of our study were less number of cases who underwent LAVH and retrospective nature of the study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Nevertheless this bearing on cost could be overcome by early return to work after LAVH. 10 Main drawbacks of our study were less number of cases who underwent LAVH and retrospective nature of the study.…”
Section: Discussionmentioning
confidence: 94%
“…Similar to the other studies we compared with, our study too showed that none of the patients following LAVH needed additional analgesics. Whereas 10.1% (10) patients following TAH required additional analgesics. 5 Average fall in haemoglobin concentration was 1.05 gm% in TAH group and 0.95gm% in LAVH group which was comparable.…”
Section: Discussionmentioning
confidence: 95%
“…Reduction in surgical site infections is associated with minimally invasive surgeries. A review of laparoscopically assisted vaginal hysterectomy and vaginal hysterectomies at a tertiary diabetes hospital in Bangladesh showed an average febrile morbidity of 1.6% and urinary tract infections of 1.2%, which is considerably lower than that for laparotomy cases [19].…”
Section: Review Of Existing Literature On Hospital Acquired Infectionmentioning
confidence: 93%
“…[ 4 ] Studies have suggested that the benefit of minimally invasive surgeries over abdominal hysterectomy is in terms of acceptability and less duration of hospital stay and early resumption of work, but these surgeries need special skills that can be developed with time. [ 4 5 ] NDVH has the advantage of being scarless as compared to TLH and LAVH whereas it is not suitable for removing large size uterus. [ 6 ] LAVH and TLH have an advantage over NDVH because significantly large-size uterus can be removed without a large abdominal incision in the presence of pelvic pathology, adnexal mass, adhesions, and endometriosis by a skilled surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Laparoscopic hysterectomies take increased operating time and increased rate of intraoperative complications, so lack of expertise and inexperience has a major impact in choosing the route of surgery. [ 5 ] This study was done to compare the feasibility of the different methods of hysterectomies for treatment of benign uterine disease in our rural tertiary care to find out the most effective, safe, feasible method in terms of operative time, amount of blood loss, hospital stay, amount of analgesic required on the 1 st postoperative day of surgery, intra- and postoperative complications rate, and postoperative duration of hospital stay.…”
Section: Introductionmentioning
confidence: 99%